Nucleon Momentum Distributions and Elastic Electron Scattering from 59Co, 61Ni, 63Cu and 65Cu Nuclei - Al–Rahmani, A. Abdul Majeed; Kadhim, Yasemain Hassan (Al-Nahrain Journal of Science, 2018)
The nucleon momentum distributions (NMD) and the elastic electron scattering form factors F(q) of the ground state for some 1f-2p shell nuclei for 59Co, 61Ni, 63Cu and 65Cu are calculated using the Coherent Density Fluctuation Model (CDFM) and expressed in terms of the fluctuation function (weight function) . The fluctuation function has been related to the nucleon density distribution (NDD) of the nuclei and determined from the theory and experiment. The property of the long-tail behavior at high momentum region of the NMD has been obtained by both the theoretical and experimental fluctuation functions. The calculated form factors of all nuclei under study are in good agreement with those of experimental data throughout all values of momentum transfer